The Impact of Fintech Implementation and Digital Financial Literacy on Financial Inclusion in Bangkalan Regency - Achmad Febrianto; Nurul Imamiyah (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the effect of financial technology (fintech) implementation and digital financial literacy on financial inclusion among residents of Bangkalan Regency, both partially and simultaneously. This study uses a quantitative approach with a causal associative design. Data were collected through questionnaires distributed to 42 respondents selected using a purposive sampling technique. Data analysis was performed using multiple linear regression with the help of IBM SPSS Statistics software. Prior to analysis, the research instrument had met validity and reliability tests and passed the classical assumption test, including normality, multicollinearity, and heteroscedasticity. The results show that fintech implementation has a positive and significant effect on financial inclusion with a significance value of 0.043 (> 0.05). Digital financial literacy also has a positive and significant effect on financial inclusion with a significance value of 0.000 (< 0.05) and is the most dominant variable with a regression coefficient of 0.742 and a beta value of 0.745. The simultaneous test results show that the implementation of fintech and digital financial literacy together have a significant influence on financial inclusion with a measured F value of 91.300 and a significance level of 0.000. The adjusted R Square value of 0.815 indicates that these two variables explain 81.5% of the variation in community financial inclusion in Bangkalan Regency.